Correlation between Early Maladaptive Schemas with Automatic Negative Thoughts and Health Anxiety among School Students - Faezeh Ebrahimi sadr; Abbas Bakhshipour (Shiraz University of Medical Sciences, 2022)
Although health anxiety is a rare type of anxiety in adolescents and children, it has a negative impact on their mental health. Health anxiety refers to worries and fears about one's health and physical sensations. The current study aimed to examine the correlation of early maladaptive schemas with automatic negative thoughts and health anxiety in school students.This correlational research was conducted in 2022 in Tabriz, Iran. The participants were 200 students recruited through convenience sampling method. To collect data, we used the Health Anxiety Inventory, Automatic Thoughts Questionnaire, and the Young Schema Questionnaire- Short. The early maladaptive schema's factors were significantly correlated with health anxiety and automatic negative thoughts (P=0.001). Early maladaptive schemas are pervasive dysfunctional themes or patterns that negatively impress people's thoughts and lead to misinterpretations about internal and external events.